Astrofísica de partículas na sala de aula : uma sequência de ensino e aprendizagem sobre raios cósmicos para o ensino médio - Saran, Marina Cláudia Brustello (2012)
Updating the physics curriculum for high school has been a challenge to all researchers and teachers in the area for at least two decades and has appeared in many academic studies that account for the needs justifying this update. However, we still haven´t achieved this update in the classrooms. But there is already some research focused on structure and activities for teaching and learning sequences that have emerged in the field of physics education research in order to fill this gap in the curriculum of physics for high school. From this research we reflected on the possibilities of carrying out a process of transformation in regards to the theme of cosmic rays in learning how to teach, based on the rules and features of the Theory of Didactic Transposition, proposed by Ives Chevallard (1991). Thus, we implemented a sequence of teaching and learning about cosmic rays in order to determine the point of impact and reconstruct the direction of arrival of a primary cosmic ray from data recorded by the Pierre Auger Observatory. We applied this activity in the form of a mini course in a public school in the city of Sertãozinho/SP. This activity addressed fundamental concepts such as energy conservation, center of mass, velocity, coordinate systems, time references and observation of the sky.